Return fire - Gonzalez, Christina Diaz, 1969- (Scholastic Press, 2016)
Just after Cassie Arroyo found the Spear of Destiny in Rome, it was stolen from her, so now she and her friend Asher must recover it--but when she used the Spear before she set the world down a dangerous path, and if she recovers it she will have to decide whether to risk using it again.